2000
DOI: 10.1093/jexbot/51.342.9
|View full text |Cite
|
Sign up to set email alerts
|

Wild barley: a source of genes for crop improvement in the 21st century?

Abstract: The development of new barleys tolerant of abiotic and biotic stresses is an essential part of the continued improvement of the crop. The domestication of barley, as in many crops, resulted in a marked truncation of the genetical variation present in wild populations. This process is significant to agronomists and scientists because a lack of allelic variation will prevent the development of adapted cultivars and hinder the investigation of the genetic mechanisms underlying performance. Wild barley would be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
107
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(108 citation statements)
references
References 27 publications
1
107
0
Order By: Relevance
“…To what extent the apparent genetic variation in barley will translate into tolerance to the prevailing abiotic stress under climate change is yet unexplored. If not present in the present crop cultivars, this highly requested environmental tolerance might be found in the landraces or cross compatible wild relatives (Ellis et al 2000;Newton et al 2010). In a long term monitoring program Nevo et al (2012) for example found that natural climate stress created profound adaptive changes in wild barley (Hordeum spontaneum K. Koch).…”
Section: Introductionmentioning
confidence: 96%
“…To what extent the apparent genetic variation in barley will translate into tolerance to the prevailing abiotic stress under climate change is yet unexplored. If not present in the present crop cultivars, this highly requested environmental tolerance might be found in the landraces or cross compatible wild relatives (Ellis et al 2000;Newton et al 2010). In a long term monitoring program Nevo et al (2012) for example found that natural climate stress created profound adaptive changes in wild barley (Hordeum spontaneum K. Koch).…”
Section: Introductionmentioning
confidence: 96%
“…The introgression of genomic segments from wild to cultivated barley has been a useful procedure for increasing the genetic variation of traits that contribute to drought tolerance (Lakew et al, 2011). However, only 40% of wild barley alleles are represented in cultivated barley (Ellis et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Disomic addition lines, in which a single pair of chromosomes from a related species is added to the full chromosome complement of the recipient, can be used to identify chromosomes carrying the genes controlling adaptation and phenotypic stability, and form the starting point for gene transfer and the genetic improvement of genotypic stability (Ellis et al, 2000;Farshadfar, 2008).…”
Section: Introductionmentioning
confidence: 99%